Environmental effects on the construction and physical properties of Bombyx mori cocoons - Offord, C; Vollrath, F; Holland, C (Springer US, 2016)
Published studies of silks focus on processed fibres or the optimum conditions for their production. Consequently, the effects of the environment on the physical properties of the cocoon are either poorly understood or kept as closely guarded industrial secrets. In this study, we test the hypothesis that silkworms as ectothermic animals respond to environmental conditions by modifying their spinning behaviour in a predictable manner, which affects the material properties of the cocoons in predictable ways. Our experiments subjected spinning Bombyx mori silkworms to a range of temperatures and relative humidities that, as we show, affect the morphology and mechanical properties of the cocoon. Specifically, temperature affects cocoon morphology as well as its stiffness and strength, which we attribute to altered spinning behaviour and sericin curing time. Relative humidity affects cocoon colouration, perhaps due to tanning agents. Finally, the water content of a cocoon modifies sericin distribution and stiffness without changing toughness. Our results demonstrate environmentally induced quality parameters that must not be ignored when analysing and deploying silk cocoons, silk filaments or silk-derived bio-polymers.